Stress state of thin – walled member of the structure with operation damages under nonuniform loading - Астанін, В.В.; Бородачов, М.М.; Сирота, Н.О. (Proceedings of National Aviation University (archive), 2012)
The publication is dedicated to determining of stress state in particular the stress concentration factors for thin – walled members of the structures subject to nonuniform tension. A structure member has obtained the operation damage generation by corrosion and other causes.